The Effects of Elaeagnus angustifolia L. on the Thyroid-Stimulating Hormone, Dehydroepiandrosterone-Sulfate, Prolactin and Cortisol Levels in Post-Menopausal Women: A Double-Blind, Randomized, and Placebo-Controlled Study - Jalalvand, Fatemeh; Rezaei, Arezou; Badehnoosh, Bita; Yaseri, Mehdi; Qorbani, Mostafa; Emaminia, Farzaneh; Shabani, Mahzad (Frontiers in Pharmacology, 2021)
Menopause is the last menstrual period associated with a decline in ovarian steroid secretion and follicular loss. Hormone profile changes during menopause include a decrease in the production of estrogen, dehydroepiandrosterone (DHEA), and prolactin (PRL), and an increase in thyroid-stimulating hormone (TSH) and cortisol. Herbal medicines are considered alternatives to hormone therapy. The studies on postmenopausal women have shown that Elaeagnus angustifolia L. (called "Senjed" in Persian) has some efficacy in improving sex hormone and lipid profiles, joint pain, and cardiovascular function, as the decrease in luteinizing hormone, low-density lipoprotein, and heart rate was significant. The aim of the present study was to evaluate the effects of E. angustifolia on TSH, DHEA-S, PRL, and cortisol levels and their ratios in postmenopausal women. It is assumed that the eventual effects of hormones on the brain and other tissues are determined by the balance between interdependent hormones. In the present randomized double-blinded placebo-controlled trial (https://en.irct.ir/search/result?query=IRCT20170227032795N4), fifty-eight postmenopausal women were randomly assigned to one of two medicinal herb (15 g of the whole E. angustifolia fruit powder) and placebo (7.5 g isomalt + 7.5 g cornstarch) groups. After ten weeks of the treatment, the serum levels of TSH, DHEA-S, PRL, cortisol hormones, and their ratios were measured. The increase in the TSH, and cortisol levels, and cortisol/DHEA-S ratio and the decrease in prolactin and DHEA-S and the PRL/TSH, PRL/cortisol, and DHEA-S/TSH ratios after E. angustifolia consumption were significant only based on within-group but not on the between-group analysis. Based on between-group analyses, the changes in the hormone profile were not significant in the placebo group. According to Iranian tradition and folklore, E. angustifolia fruit is a symbol of female fertility. Therefore, its consumption is highly recommended to maintain health in the elderly, especially women. However, the observed outcomes about the effect of E. angustifolia on menopause were not completely in line with the Iranian folklore. E. angustifolia consumption did not significantly affect the hormone profile and ratios at the end of the ten-week trial, possibly due to the small sample size, short time, and the fact that our participants were postmenopausal women.